2017
DOI: 10.1159/000480362
|View full text |Cite
|
Sign up to set email alerts
|

The Nrf2/HO-1 Pathway Mediates the Antagonist Effect of L-Arginine On Renal Ischemia/Reperfusion Injury in Rats

Abstract: Background/Aims: Ischemia/reperfusion (I/R) is the most common cause of acute renal injury. I/R-induced oxidative stress is involved in the development of acute renal injury, which can be reversed by supplementation with L-arginine, a precursor of nitric oxide (NO). This study was conducted to evaluate alterations in the expression of transcription factors [nuclear factor kappa B (NF-κB), nuclear factor-E2-related factor-2 (Nrf2), and heme oxygenase 1 (HO-1)] and heat shock protein 70 (HSP70) in the kidney of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 45 publications
0
19
1
Order By: Relevance
“…Several strategies to induce HO-1 apart from the traditional porphyrin-based compounds and heme have been reported. These include targeting of the nuclear factor (erythroid-derived 2)-like 2 (NFE2L2 and Nrf2, respectively) [121,122,123], and treatment with resveratrol and electroacupuncture [124,125]. One area in which research into the protective actions of HO induction is lacking is in large animal models of cardiovascular and renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies to induce HO-1 apart from the traditional porphyrin-based compounds and heme have been reported. These include targeting of the nuclear factor (erythroid-derived 2)-like 2 (NFE2L2 and Nrf2, respectively) [121,122,123], and treatment with resveratrol and electroacupuncture [124,125]. One area in which research into the protective actions of HO induction is lacking is in large animal models of cardiovascular and renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…classical mechanical hypotheses suggest that cro protected against I/R injury in the brain and heart via an antioxidant response. However, previous studies demonstrated that inflammation served an important role in reperfusion injury, causing a secondary cascade of lethal damage (2,12). Therefore, it was suggested that CRO had the ability to reduce the inflammatory response induced by reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…In Nrf2-deficient mice, the cardiovascular phenotype is more impaired, even in the ischemic preconditioning model, due to its important function in the cardiovascular system (9). Previous studies demonstrated that Nrf2/heme oxygenase-1 (HO-1) signaling plays an important role in I/R injury in different organs (10)(11)(12)(13). Activation of Nrf2/HO-1 signaling is an effective method to attenuate myocardial I/R injury in several previous pharmacological studies (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Nrf2, a redox-sensitive transcription factor, is crucial to inhibit oxidative stress in cells (Gallorini et al, 2015). Once activated, Nrf2 can transactivate genes driven by antioxidant response elements (ARE), especially HO-1 (Tong and Zhou, 2017). Herein, it has been reported that the Nrf2/HO-1 pathway exhibits protective roles in ischemic disorders, including MI (Zeng et al, 2015).…”
Section: Inhibition Of Oxidative Stressmentioning
confidence: 99%